2003
DOI: 10.1063/1.1575210
|View full text |Cite
|
Sign up to set email alerts
|

State resolved inelastic scattering of N2 from Ru(0001)

Abstract: Detailed measurements of state resolved inelastic scattering of N2 from Ru(0001) are reported for a wide range of initial energies (0–3 eV) and angles of incidence. The ion time-of-flight resonantly enhanced multiphoton ionization (REMPI) detection scheme developed here and used with cw molecular beams simultaneously measures the internal quantum state and translational energy normal to the sample surface. Doppler broadening of the REMPI spectrum of scattered particles yields the dispersion in scattering out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 51 publications
4
48
0
Order By: Relevance
“…As it was shown in Refs. 30 and 31, these theoretical results reproduce the surprisingly low dissociation probabilities [27,[50][51][52] found in the experiments. The results can be understood based on the very special characteristics of the N 2 /Ru(0001) PES: [28,30,31,51] The minimum barrier is very high, around 2.3 eV, and the PES displays high anisotropy and corrugation, i.e., small changes in the orientation and/or the position of the molecule gives rise to large changes in the potential energy (see Fig.…”
Section: A 6d Dynamics and The Vibrational Efficacysupporting
confidence: 79%
“…As it was shown in Refs. 30 and 31, these theoretical results reproduce the surprisingly low dissociation probabilities [27,[50][51][52] found in the experiments. The results can be understood based on the very special characteristics of the N 2 /Ru(0001) PES: [28,30,31,51] The minimum barrier is very high, around 2.3 eV, and the PES displays high anisotropy and corrugation, i.e., small changes in the orientation and/or the position of the molecule gives rise to large changes in the potential energy (see Fig.…”
Section: A 6d Dynamics and The Vibrational Efficacysupporting
confidence: 79%
“…Previous studies of rare-gas and diatomic molecular scattering from clean Ru(0001) have revealed a large effective mass. An analysis of the energy-resolved spectra of Ar scattering from Ru(0001) [42,43] as well as scattering of N 2 molecules from similar Ru(0001) [44,45] gave for both projectile particles an effective mass of approximately 2.5 Ru atoms. Based on the analysis of those two systems it was proposed that the Ru(0001) surface would present a large effective mass for the scattering of all the rare gases and even for other projectiles [46].…”
Section: Surface Effective Masses From Ar Scatteringmentioning
confidence: 99%
“…6 No isotope effect has been observed in the classical regime ͑E i ജ V * ͒, but for lower energies the reaction probability for 15 N 2 is smaller than for 14 N 2 , which has been interpreted in terms of tunneling through a large barrier for dissociation. 6 Another unexpected feature is the lack of vibrational excitation in molecularbeam experiments for N 2 scattering from Ru͑0001͒, 13 and the small amount of vibrational excitation observed in laser assisted associative desorption ͑LAAD͒, 11 associative desorption being the reverse process to dissociative chemisorption. Late barrier systems ͑reaction barrier found for an extended vibrational coordinate͒ are expected to exhibit significant vibrational excitation of the molecule upon scat-tering and associative desorption.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of this interest a large number of experimental [1][2][3][4][5][6][7][8][9][10][11][12][13] and theoretical 5,11,14 studies have been published, showing unusual and sometimes controversial results. Although recent theoretical and experimental work [15][16][17] has proved that dissociation at Ru steps is much more efficient than at the Ru͑0001͒ terraces, N 2 /Ru͑0001͒ is of much fundamental interest.…”
Section: Introductionmentioning
confidence: 99%